CONSIDERATIONS REGARDING THE PERFORMANCE OF GROUPS OF COMPANIES - Mariana BANUTA; Mihaela GADOIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2021)
Groups of companies represent a poignant reality of the economy of the most recent the decades, and their importance is proved by the expansion of the grouping phenomenon, the economic power they have at international/national level, as well as by the interest of information users in the wealth of groups, their performance and also their strategies. Our article presents aspects that bring to the forefront the manner of reflecting performance from the perspective of the aspects monitored by information users, or how the latter also see performance from the perspective of the information provided through the consolidated financial statement. We believe that highlighting certain fiscal aspect will raise interest, in addition to the accounting treatment and the manner of how performance is analysed at the level of groups of companies.